Vitamin D and safe journey - Shamim Shakiba; Mehrdad Shakiba (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
We present a hypothesis for low vitamin D as a sign of untimely relocation of the human being during its history. This improper displacement prone our species to infectious and non-infectious diseases during our life journey, low vitamin D is a sign that needs to be addressed as a marker of the unsafe journey in our lifetime not the cause for diseases that are associated with it and replacement of vitamin D is the least that we have done.